2018
DOI: 10.1111/cmi.12965
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CEACAM1 or CEACAM5 in AZ-521 cells restores the type IV secretion deficiency for translocation of CagA byHelicobacter pylori

Abstract: Helicobacter pylori represents an important pathogen involved in diseases ranging from gastritis, peptic ulceration, to gastric malignancies. Prominent virulence factors comprise the vacuolating cytotoxin VacA and the cytotoxin-associated genes pathogenicity island (cagPAI)-encoded type IV secretion system (T4SS). The T4SS effector protein CagA can be translocated into AGS and other gastric epithelial cells followed by phosphorylation through c-Src and c-Abl tyrosin kinases to hijack signalling networks. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 81 publications
1
26
1
Order By: Relevance
“…Studying the structural elements of HopQ-CEACAM interaction has allowed us to demonstrate a key and specific role for disulfide bonds in H. pylori virulence, but, more importantly, offered a broader view of the larger network of proteins that supports what initially seems a straightforward protein-protein interaction. Although HopQ has been proposed to interact with the T4SS [35], the impaired CagA-translocation observed in our study is a result of the binding defect induced by the mutations inserted. The clear importance of Dsb-like proteins to H. pylori infection, whether it be HopQ binding, CagA translocation or others, prompts further work to precisely identify their contributions and further our understanding of their roles.…”
Section: Discussioncontrasting
confidence: 59%
“…Studying the structural elements of HopQ-CEACAM interaction has allowed us to demonstrate a key and specific role for disulfide bonds in H. pylori virulence, but, more importantly, offered a broader view of the larger network of proteins that supports what initially seems a straightforward protein-protein interaction. Although HopQ has been proposed to interact with the T4SS [35], the impaired CagA-translocation observed in our study is a result of the binding defect induced by the mutations inserted. The clear importance of Dsb-like proteins to H. pylori infection, whether it be HopQ binding, CagA translocation or others, prompts further work to precisely identify their contributions and further our understanding of their roles.…”
Section: Discussioncontrasting
confidence: 59%
“…To elucidate why CagA was not delivered into the oral cells, we investigated whether these cell types expressed CEACAM receptors. Previous Western blotting studies had revealed that AGS cells expressed three T4SSrelevant CEACAM members, sized approximately 120, 180 and 90 kDa, corresponding to CEACAM members 1, 5 and 6, respectively [22,23,26]. Here, we subjected uninfected HN, CAL-27 and BHY cells to flow cytometry and used monoclonal antibodies specific for detection of each of these three CEACAM members (Fig.…”
Section: The Role Of Ceacam Members In Caga Internalization By Infectmentioning
confidence: 99%
“…Most of the known gastric epithelial cell lines can express CEACAM receptors and permit CagA injection [22][23][24][25][26]. However, whether CEACAM receptors play a role in bacterial colonization of the oral cavity has not been studied yet.…”
mentioning
confidence: 99%
“…Activation of CEACAM1 by CEACAM1 leads to the inhibition of immune cell activities, whereas the Opa activation of CEACAM1 impairs normal maturation of immature dendritic cells, suppresses lymphocyte responses to activating stimuli, and also impairs phagocytic engulfment of the bacteria. 13 CEACAM1 also binds HopQ which enables CagA translocation [14][15][16] and also protects tumors from immune cell attack. 17 CEACAM1 is expressed on the surface of a wide variety of tumors, and is considered to be a specific biomarker associated with tumor progression, metastasis and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%